Lability and bioavailability of Co, Fe, Pb, U and Zn in a uranium mining restoration site using DGT and phytoscreening - Gemeiner, Hendryk [UNESP]; Menegário, Amauri Antonio [UNESP]; Williams, Paul N.; Matavelli Rosa, Amália E.; Santos, Cristiane A. [UNESP]; Pedrobom, Jorge Henrique [UNESP]; Elias, Lucas Pellegrini [UNESP]; Chang, Hung Kiang [UNESP] (Springer Nature, 2021)
Mine restoration is a long and ongoing process, requiring careful management, which must be informed by site-specific, geochemical risk assessment. Paired topsoil and tree core samples from 4 sites within the uranium mining complex of INB Caldas in Minas Gerais (Brazil) were collected. Soil samples were analysed for their total content of Co, Fe, Pb, U and Zn by XRF, and subsequently, the potential environmental bioavailability of these metals were investigated by DGT and pore water analysis. In addition, results were compared with metal concentrations obtained by Tree Coring from the forest vegetation. In all sampling areas, mean total concentrations of U (Ctot. = 100.5 ± 66.5 to 129.6 ± 57.1 mg kg−1), Pb (Ctot. = 30.8 ± 12.7 to 90.8 ± 90.8 mg kg−1), Zn (Ctot. = 91.5 ± 24.7 to 99.6 ± 10.3 mg kg−1) and Co (Ctot. = 73.8 ± 25.5 to 119.7 ± 26.4 mg kg−1) in soils exceeded respective quality reference values. Study results suggest that AMD caused the increase of labile concentrations of Zn in affected soils. The high lability of the elements Pb (R = 62 ± 34 to 81 ± 29%), U (R = 57 ± 20 to 77 ± 28%) and Zn (R = 21 ± 25 to 34 ± 31%) in soils together with high bioconcentration factors found in wood samples for Pb (BCF = 0.0004 ± 0.0003 to 0.0026 ± 0.0033) and Zn (BCF = 0.012 ± 0.013 to 0.025 ± 0.021) indicated a high toxic potential of these elements to the biota in the soils of the study site. The combination of pore water and DGT analysis with Tree Coring showed to be a useful approach to specify the risk of metal polluted soils. However, the comparison of the results from DGT and Tree Coring could not predict the uptake of metals into the xylems of the sampled tree individuals.
Keywords: Bioavailability; DGT; Metal lability; Phytoscreening; Soil contamination; Uranium mining